2019
DOI: 10.3389/fmicb.2019.00460
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Antibiotic Resistance Determinants in Forest and Grassland Soil Metagenomes

Abstract: Soil represents a significant reservoir of antibiotic resistance genes (ARGs), which can potentially spread across distinct ecosystems and be acquired by pathogens threatening human as well as animal health. Currently, information on the identity and diversity of these genes, enabling anticipation of possible future resistance development in clinical environments and the livestock sector, is lacking. In this study, we applied functional metagenomics to discover novel sulfonamide as well as tetracycline resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
(61 reference statements)
0
22
0
Order By: Relevance
“…Furthermore, a transposase gene, ISPme1, was also identified upstream of BlaCM1, indicating that the antibiotic resistant gene might be mobile. Novel sulfonamide resistance genes AEW9_dhps01, SEW2_dhps01, and SEW5_dhps01, and AEG2_DHPS01 were also detected in forest and grassland soils from Germany, which were relatively unexposed to human intervention (Willms et al, 2019). The study also identified major facilitator superfamily (MFS) efflux pump mediated tetracycline resistance.…”
Section: Discoveries In Novel Antibiotics Resistant Genes Through Expmentioning
confidence: 80%
“…Furthermore, a transposase gene, ISPme1, was also identified upstream of BlaCM1, indicating that the antibiotic resistant gene might be mobile. Novel sulfonamide resistance genes AEW9_dhps01, SEW2_dhps01, and SEW5_dhps01, and AEG2_DHPS01 were also detected in forest and grassland soils from Germany, which were relatively unexposed to human intervention (Willms et al, 2019). The study also identified major facilitator superfamily (MFS) efflux pump mediated tetracycline resistance.…”
Section: Discoveries In Novel Antibiotics Resistant Genes Through Expmentioning
confidence: 80%
“…The metagenomic libraries AEW1, AEW5, SEG8 and SEW5, used for function-based screening, were reported previously [ 26 , 27 ], whereas library AEW4 was constructed in this study as described by Nacke et al [ 26 ]. Names of the metagenomic libraries refer to the designation of soil samples from which the libraries were derived.…”
Section: Methodsmentioning
confidence: 99%
“…Names of the metagenomic libraries refer to the designation of soil samples from which the libraries were derived. The samples AEW1, AEW4 and AEW5 represent spruce (AEW1) and beech (AEW4 and AEW5) forest soil collected within the German Biodiversity Exploratory Schwäbische Alb, whereas the samples SEG8 and SEW5 represent grassland (non-fertilized pasture) and beech forest soil, respectively, collected within the German Biodiversity Exploratory Schorfheide-Chorin [ 26 , 27 , 53 ]. All samples were derived from A horizons (topsoil) and metagenomic libraries were constructed using the plasmid pCR-XL-TOPO (Thermo Fisher Scientific, Braunschweig, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, even remote environments or the sponge microbiota may host AMR genes or plasmids [ 84 , 96 ], and novel antibiotic resistance determinants have been also discovered in forest and grassland soil metagenomes [ 97 ], thus hosting diverse and novel resistance genes that may be harnessed by phylogenetically distinct bacteria and may act as a reservoir of functional resistance genes [ 98 ]. The occurrence of MDR bacteria in wildlife is clearly influenced by many and different factors that have not yet been fully understood [ 99 , 100 ].…”
Section: Amr In the Environmentmentioning
confidence: 99%